Mechanism of transcription termination: PTRF interacts with the largest subunit of RNA polymerase I and dissociates paused transcription complexes from yeast and mouse - Jansa, Pavel; Grummt, Ingrid (Molecular genetics and genomics, 1999)
Transcription termination by RNA polymerase I (Pol I) is a stepwise process. First the elongating RNA polymerase is forced to pause by DNA-bound transcription termination factor (TTF-I). Then the ternary transcription complex is dissociated by PTRF, a novel factor that promotes release of both nascent transcripts and Pol I from the template. In this study we have investigated the ability of PTRF to liberate transcripts from ternary transcription complexes isolated from yeast and mouse. Using immobilized, tailed templates that contain terminator sequences from Saccharomyces cerevisiae and mouse, respectively, we demonstrate that PTRF promotes release of terminated transcripts, irrespective of whether mouse Pol I has interacted with the murine termination factor TTF-I or its yeast homolog Reb1p. In contrast, mouse Pol I paused by the lac repressor remains bound to the template both in the presence and absence of PTRF. We demonstrate that PTRF interacts with the largest subunit of murine Pol I, with TTF-I and Reb1p, but not the lac repressor. The results imply that Pol I transcription termination in yeast and mouse is mediated by conserved interactions between Pol I, Reb1p/TTF-I and PTRF.
Gesehen am 30.03.2020